2015
DOI: 10.1093/nar/gkv826
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine and 8-oxoguanine in G-quadruplexes: formation of a G·G·X·O tetrad

Abstract: G-quadruplexes are four-stranded structures built from stacked G-tetrads (G·G·G·G), which are planar cyclical assemblies of four guanine bases interacting through Hoogsteen hydrogen bonds. A G-quadruplex containing a single guanine analog substitution, such as 8-oxoguanine (O) or xanthine (X), would suffer from a loss of a Hoogsteen hydrogen bond within a G-tetrad and/or potential steric hindrance. We show that a proper arrangement of O and X bases can reestablish the hydrogen-bond pattern within a G·G·X·O tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 63 publications
3
38
0
Order By: Relevance
“…3a, all folded sequences exhibited positive and negative peaks at 279 and 295 nm, respectively, in agreement with G4 formation, with or without oxidative damage. These results were consistent with previous reports that G4s can withstand G-to-8-oxoG mutations 36,39,40 . Next, circular dichroism (CD) spectra showed that the incorporation of 8-oxoG in G3TC and G3A preserved the parallel topology of the parent sequences, as evidenced by positive and negative peaks at ca.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…3a, all folded sequences exhibited positive and negative peaks at 279 and 295 nm, respectively, in agreement with G4 formation, with or without oxidative damage. These results were consistent with previous reports that G4s can withstand G-to-8-oxoG mutations 36,39,40 . Next, circular dichroism (CD) spectra showed that the incorporation of 8-oxoG in G3TC and G3A preserved the parallel topology of the parent sequences, as evidenced by positive and negative peaks at ca.…”
supporting
confidence: 93%
“…The thermal stabilities of the resulting G4s were determined by UV-melting/annealing experiments ( Fig. S1, Supporting Information): the melting temperature values (Tm, summarized in Table 1) were in line with previous reports 36,39,40 that the presence of an 8-oxoG within a G4-forming sequence decreased the overall stability of the resulting G4 structure. Our results also highlight that G4s with a single 8-oxoG are quite stable, with Tm values >52 ℃.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Prior to MD simulation, K + ions were introduced around the structure computed in XPLOR, including internal placement between G-tetrads of the Gquadruplex. Structures were then solvated before undergoing a series of constrained minimization and simulation steps as previously described (54). Finally, structures were refined over 1 ns of restrained MD simulations including hydrogen-bond restraints and inter-proton distance restraints.…”
Section: Structure Calculationmentioning
confidence: 99%
“…The author has applied amino rotation determination with lineshape analysis to multiple G4 sequences to help determine their folding topology, including the fold- Structures of Novel G-quadruplex Systems G-quadruplexes adopt diverse topologies [10], with the discovery of several novel topologies widening the possibilities of efficient drug targeting via site modification [135][136][137] and facilitating the development of nano-scaffolds via G4 engineering [138]. Some G4 ligands or helicases bind or unwind a certain G4 fold specifically [139], which raise the importance of G4 fold.…”
Section: Future Workmentioning
confidence: 99%